Pólen apícola coletado por abelhas Apis mellifera L. (africanizadas) no semiárido potiguar - Medeiros, Anna Jacinta Dantas de (2017)
Bee pollen is an indispensable raw material for the development of colonies and has several applications. It is derived from the joining of pollen grains with nectar and / or honey and honey salivary substancesofApis melliferaand represents an important source of income for beekeepers. However, the scarcity of information about the pollen flora and its contribution to the nutritional characteristics of pollen are still obstacles in the expansion of its production.In this sense, the present study aimed to analyze the botanical origin, physicochemical characteristics, amino acid composition and identification of the present bee pollen compounds collected in the apiaries located in the National Forest of Assú/RN (FLONA) and at the Rafael Fernandes Experimental Farm Federal Rural University of the Semi-Arid (UFERSA), localities of the Brazilian semiarid. For this, 54 pollen samples were obtained during September 2014 to October 2015. Palynological analysis and determinationof the levels of ashes, proteins, lipids, carbohydrates, total phenolics, flavonoids and antioxidant activity (DPPH) were carried out. Finally, the profile of the amino acids and the constituents of the chloroform and hydrometanolic extract were determined. It was observed that the bees' diet in Assúwas composed of 66 pollen types distributed in 32 families. In Mossoró, 44 pollen types and 21 families were identified. In both locations, the most representative botanical family was Fabaceae. In the rainy season the amount of bee pollen retained in the collectors and numbers of collected pollen types increased. As for the centesimal composition, it varied during the experiment and the highest levels were carbohydrates (81.11 ± 0.55 to 66.97 ± 1.30%) and proteins (13.33 ± 0.10 to 25, 59 ± 0.12%) and the lowest ash (2.08 ± 0.18 to 5.00 ± 0.16%) and lipids (2.60 ± 0.20 to 4.86 ± 0.03%). On the quantification of the biocomposites, there were oscillations in total phenol contents (7.68 ± 0.02 at 70.31 ± 0.29 mg GAE / g), flavonoids (1.68 ± 0.14 at 49.03 ± 0, 16 mg QE / g) and antioxidant activity (78.96 ± 0.82 at 96.42 ± 0.83%) during the collection period. It was also verified that the highest indexes of polyphenols and flavonoids were found in samples with high relative frequency of the pollen type Mimosa tenuiflora. As regards the monofloral pollen analysis of Anacardium occidentaleL. and Mimosa tenuiflora, eighteen amino acids were present in both matrices, including the ten essential amino acids. Among them, aspartic acid and glutamic acid were the predominant ones. All amino acids, except tryptophan present in jurema-black pollen, were in amounts greater than the recommended percentages of the bees and human diet. The lipid fraction of the cashew extract and the black jurema presented 11 and 9 constituents, respectively. In the polar fraction 21 compounds were detected in the pollen extract of the Anacardium occidentaleL. and 31 substances in the Mimosa tenuifloraextract. This study shows that in the Brazilian semi-arid there is a diversity of plants, both in the dry and rainy season, with potential for the production of bee pollen